Engineering the Near‐Surface of PtRu3 Nanoparticles to Improve Hydrogen Oxidation Activity in Alkaline Electrolyte. Issue 6 (20th January 2021) - Zhang, Junming; Qu, Ximing; Shen, Linfan; Li, Guang; Zhang, Tianen; Zheng, Jinhong; Ji, Lifei; Yan, Wei; Han, Yu; Cheng, Xiaoyang; Jiang, Yanxia; Sun, Shigang
Abstract: Tailoring the near‐surface composition of Pt‐based alloy can optimize the surface chemical properties of a nanocatalyst and further improve the sluggish H2 electrooxidation performance in an alkaline electrolyte. However, the construction of alloy nanomaterials with a precise near‐surface composition and smaller particle size still needs to overcome huge obstacles. Herein, ultra‐small PtRu3 binary nanoparticles (<2 nm) evenly distributed on porous carbon (PtRu3 /PC), with different near‐surface atomic compositions (Pt‐increased and Ru‐increased), are successfully synthesized. XPS characterizations and electrochemical test confirm the transformation of a near‐surface atomic composition after annealing PtRu3 /PC‐300 alloy; when annealing in CO atmosphere, forming the Pt‐increased near‐surface structure (500 °C), while the Ru‐increased near‐surface structure appears in an Ar heat treatment process (700 °C). Furthermore, three PtRu3 /PC nanocatalysts all weaken the hydrogen binding strength relative to the Pt/PC. Remarkably, the Ru‐increased nanocatalyst exhibits up to 38.8‐fold and 9.2‐fold HOR improvement in mass activity and exchange current density, compared with the Pt/PC counterpart, respectively. CO‐stripping voltammetry tests demonstrate the anti‐CO poisoning ability of nanocatalysts, in the sequence of Ru‐increased ≥ PtRu3 /PC‐300 > Pt‐increased > Pt/PC. From the perspective of engineering a near‐surface structure, this study may open up a new route for the development of high‐efficiency electrocatalysts with a strong electronic effect and oxophilic effect. Abstract : PtRu3 /PC nanocatalysts with the same bulk composition and a different near‐surface atomic composition have been successfully synthesized via a controlled thermal treatment method. The Ru‐increased nanocatalyst with the strongest electronic effect and oxophilic effect exhibits up to 38.8‐fold and 9.2‐fold HOR improvement in mass activity and exchange current density, compared with the Pt/PC counterpart, respectively.